FORMINS: THE MULTITASKING ACTIN NUCLEATORS IN DENDRITIC CELL BIOLOGY, A LITERATURE REVIEW - Simon, Claudio Roberto; da Silva, Saulo Fernando Moreira; Michelin, Márcia Antoniazi (Acta Biologica Brasiliensia, 2025)
Dendritic cells (DCs) are at the frontline of the immune defense. They are professional antigen-presenting cells capable of linking adaptive and innate Immune responses by interacting with T cells and by secreting cytokines. By performing such activities, they play an ambiguous role, either engaging the adequate immune response or initiating diseases, and thus, they pose as important therapeutic targets for immunotherapies. Such potential is even more significant if we consider the dynamics of the actin cytoskeleton remodeling to perform such roles. The Formin family of actin nucleators performs one of the three actin-regulatory networks. Formins play essential roles in virtually all eukaryotic cells, including DCs. In this way, we reviewed the most prominent functions of formins in DC biology. The most prominent formins playing roles were members of the Diaphanous and FHOS/FHOD subtypes, acting from pathogen recognition and uptaking, T-cell activation, formation of viral synapses/filopodia, migration stability to adhesion and could be considered as biomarkers of inactive and activated states of DCs. These important roles in DCs leave important open questions yet to be answered.